Diversity Management in the Medical Device Industry in the Light of the Results of International Empirical Research - Sitko-Lutek, Agnieszka; Ławicka-Kruk, Karolina; Jakubiak, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The article aims to identify and evaluate the diversity management practices used in enterprises as well as the benefits and difficulties of diversity management.Research Design & Methods: Empirical research was carried out in 2018–2020 using a diagnostic survey with a survey technique. The study surveyed 130 managers representing various medical device industry enterprises from four countries – Germany, Great Britain, France, and Poland.Findings: The most frequently used diversity management practices were flexible working hours, integration activities for employees, and analysing employment structures and job satisfaction. The analysis results also confirm that the managers more often perceived the benefits of diversity management than the difficulties. At the same time, diversity management practices are implemented spontaneously in most companies.Implications / Recommendations: The results of the research may be a source of practical recommendations for companies from the medical device industry vis-à-vis the broader use of diversity management. It may help them think about how to implement such practices and activities in their everyday routines. The research presented herein focused on three selected dimensions of diversity – age, gender, and multiculturalism. In the future, wider, cross-sectional research covering wider dimensions of diversity management in more countries would be worth doing.Contribution: The presented research attempts to fill the gap in diversity management in the innovative and rapidly developing medical device industry.